The Performing Arts and the Post-Colonial Ghanaian experience: The National Symphony Orchestra in Perspective - Nii-Dortey, M.N.; Arhine, A. (African Studies Research Review NS (26.1): 37-60, 2010)
The National Symphony Orchestra was established some 50 years ago as one of several institutions to spearhead an African cultural renaissance agenda in Ghana. Of the several institutions established the orchestra was criticized the most, ostensibly for its paradoxical status as a foreign ensemble. In this article we recount the history of the national orchestra and argue that, like other indigenized colonial institutions, the debate over its cultural relevance or otherwise should focus on the use(s) to which that ensemble is put in the Ghanaian context rather than on its history of origin and instrumentation.
Keywords: Symphony; instrumentation; paradox; cultural; institution; Orchestra